Animals in the international law of armed conflict / edited by Anne Peters, Max Planck Institute for Comparative Public Law and International Law, Robert Kolb, University of Geneva, Jérôme de Hemptinne, Geneva Academy of International Humanitarian Law and Human Rights. - Peters, Anne, 1964-; Kolb, Robert; Hemptinne, Jérôme de (Cambridge University Press, 2022)
Animals are the unknown victims of armed conflicts. Wildlife populations usually decline during warfare, with disastrous repercussions on the food chain, on fragile ecosystems and precarious habitats. Belligerents take advantage of the chaos of war for poaching and trafficking of animal products. Livestock, companion, and zoo animals, highly dependent on human care, are direct victims of hostilities. The book is the first legal analysis of these issues. It maps the framework of international humanitarian law, examining which and how the concepts, principles, and rationales can be applied and adapted for a better protection of animals. The contributions inter alia discuss precautions for animal civilians, problems of animal combatants and prisoners, a specific status for veterinarian personnel, the recognition of biodiversity hotspots as specially protected zones, and the potential of enforcement mechanisms. The concluding chapter draws together novel interpretations and reform proposals.